KH Hasyim Asy'ari and the Teacher Code of Ethics: Thought Study KH. Hasyim Asy’ari on Ethics Education and Its Relevance to Modern Education in Indonesia - Siswoyo Aris Munandar; Rinda Khoirunnisfa (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2020)
Abstract: This study started with the problem of the moral crisis that hit many rites Karima learners in Indonesia increasingly pay attention to. The moral values and morals in the modern era increasingly eroded, the student became pregnant outside of wedlock, resulting in a brawl between students, rampant drug use, and abuse of students to teachers even lead to death. KH. M. Hasyim Asy’ari about education schools as well as revealing the sides of modernity that are relevant to the present condition of education. The core of this study lies in the greatness of KH. M. Hasyim Asy’ari in changing the pesantren education system starting from the intake of moralistic characters. A breakthrough is impressive and remains relevant to the existence of schools today. Concerning some of the literature about him, This research uses a literature review with qualitative research. Data were taken from newspapers, articles, journals, books and other documents. The data were analyzed using content analysis philological, where analyzes of the educational thought KH. M. Hasyim Asy’ari associated with its development in the present. The research results lead to the conclusion, 1) To describe the relevance of ethics in Islamic education teachers according to the code of conduct KH. M. Hasyim Asy’ari teachers in Indonesia. 2). To describe the thought KH. M. Hasyim Asy’ari Islamic education and ethics of teachers to students. (3). source destination educational thought by KH. M. Hasyim Asy’ari is to humanize the position as creatures who gave birth to awareness to their rights and obligations to God the creator of man, Keywords: KH. Hasyim Ashari, Teacher Ethics, Modern Education. Abstrak: Penelitian ini berawal dari permasalahan krisis akhlak karimah yang menimpa manyoritas peserta didik di Indonesia semakin memperhantikan. Nilai-nilai ahlak dan moral di era modern semakin terkikis, siswa hamil diluar nikah, sehingga mengakibatkan tawuran antarpelajar, penggunaan narkoba semakin merajalela, serta penganiayaan siswa terhadap guru yang bahkan sampai berujung kepada kematian. KH. Hasyim Asy’ari tentang pendidikan pesantren serta mengungkap sisi-sisi modernitas yang relevan dengan kondisi pendidikan masa kini. Inti Dari penelitian ini terletak pada kehebatan KH. Hasyim Asy’ari dalam merubah sistem pendidikan pesantren mulai dari asupan karakter yang bersifat moralistic. Suatu terobosan besar yang mengesankan dan tetap relevan dengan eksistensi pendidikan masa kini. Dengan merujuk pada beberapa literatur yang menyangkut dengan beliau, penelitian ini menggunakan kajian pustaka dengan jenis penelitian kualitatif. Data diambil dari Koran, artikel-artikel, jurnal, buku dan dokumen lain. Data tersebut dianalisis menggunakan analisis isi yang filologis, di mana menganalisis terhadap pemikiran pendidikan KH. Hasyim Asy’ari dikaitkan dengan perkembangannya di masa kini. Dari hasil penelitian menghasilkan kesimpulan, 1) Untuk mendeskripsikan relevansi etika guru dalam pendidikan Islam menurut KH.Hasyim Asy’ari dengan kode etik guru di dindonesia. 2). Untuk mendeskripsikan pemikiran KH. Hasyim Asy’ari pendidikan Islam dan Etika guru terhadap murid. (3). sumber tujuan pemikiran pendidikan menurut KH. Hasyim Asy’ari adalah memanusiakan pada posisinya sebagai ciptaan yang melahirkan kesadaran untuk melakukan hak dan kewajibannya kepada Tuhan pencipta manusia, inilah yang menjadi embrio lahirnya pendidikan karakter. Kata Kunci: Hasyim Asy’ari, Etika Guru, Pendidikan Modern.